Application of vine-shoot chips during winemaking and aging of Malbec and Bonarda wines - Fanzone, Martín Leandro; Catania, Anibal Alejandro; Assof, Mariela Vanesa; Jofre, Viviana Patricia; Prieto, Jorge Alejandro; Gil Quiroga, Daniela; Lacognata Sottano, Juan; Sari, Santiago Eduardo (MDPI Publication, 2022)
The growing demand in recent years for sustainable wine production has led to the management of waste and by-products. Among them, vine-shoots could be used as additives comparable to the oak fragments widely employed in enology. This work analyzes the feasibility of applying vine-shoot chips during winemaking and the aging of Malbec and Bonarda wines from Mendoza (Argentina) and evaluates their chemical and sensory impact. Toasted (CHT) and untoasted (CHWT) vine-shoot chips obtained from a Bonarda vineyard were added in Malbec and Bonarda grapes during winemaking (Experiment A): C, control; CHWT, 12 g/L; CHT, 12 g/L. Furthermore, the same treatments were applied during aging (1M, 30 days; 2M, 60 days; 4M, 120 days) to the finished wines under controlled conditions (Experiment B). The impact of vine-shoot chips during winemaking was different between varieties. For Malbec alone, CHT caused a significant decrease in tannins, anthocyanins, and polymeric pigments, and a modification of wine color. During aging, CHWT and CHT had an impact mainly at the sensory level, increasing the wine’s complexity in terms of aromatic attributes and mouthfeel. In conclusion, the proposed technology could be a simple and economical tool for red wine production of high chemical and organoleptic quality